WT1 regulates the development of the posterior taste field - Gao, Yankun (The Company of Biologists, 2014)
Despite the importance of taste in determining nutrient intake, our understanding of the processes that control the development of the peripheral taste system is lacking. Several early regulators of taste development have been identified, including sonic hedgehog, bone morphogenetic protein 4 and multiple members of the Wnt/β-catenin signaling pathway. However, the regulation of these factors, including their induction, remains poorly understood. Here, we identify a crucial role for the Wilms' tumor 1 protein (WT1) in circumvallate (CV) papillae development. WT1 is a transcription factor that is important in the normal development of multiple tissues, including both the olfactory and visual systems. In mice, WT1 expression is detectable by E12.5, when the CV taste placode begins to form. In mice lacking WT1, the CV fails to develop normally and markers of early taste development are dysregulated compared with wild type. We demonstrate that expression of the WT1 target genes Lef1, Ptch1 and Bmp4 is significantly reduced in developing tongue tissue derived from Wt1 knockout mice and that, in normal tongue, WT1 is bound to the promoter regions of these genes. Moreover, siRNA knockdown of WT1 in cultured taste cells leads to a reduction in the expression of Lef1 and Ptch1. Our data identify WT1 as a crucial transcription factor in the development of the CV through the regulation of multiple signaling pathways that have established roles in the formation and patterning of taste placodes.